The centromere-associated protein CENPU promotes cell proliferation, migration, and invasiveness in lung adenocarcinoma. (28th April 2022) - Lou, Yuqing; Lu, Jun; Zhang, Yanwei; Gu, Ping; Wang, Huimin; Qian, Fangfei; Zhou, Wensheng; Zhang, Wei; Zhong, Hua; Han, Baohui
Abstract: CENPU, encoding an important factor involved in kinetochore assembly during mitosis, is associated with shorter survival rates in lung adenocarcinoma (LUAD) patients. CENPU promotes growth rates and invasive behavior of LUAD cells; however, its mechanism of action in LUAD progression remains to be elucidated. CENPU mRNA and protein expression were elevated in LUAD tumors, and high CENPU gene expression was associated with inferior survival prognosis in LUAD patients. CENPU knockdown inhibited LUAD cell proliferation, clone formation, migration, invasion, and epithelial-mesenchymal transition (EMT) in addition to inducing cell cycle arrest and apoptosis in vitro and reduced LUAD xenograft tumor growth in vivo . Furthermore, we identified CENPU-regulated genes significantly enriched for proliferation and apoptosis pathways, and identified HSP Family Member C10 (DNAJC10) as putative effector of CENPU. CENPU knockdown produced DNAJC10 protein downregulation, and DNAJC10 overexpression partially rescued the phenotypic effects of CENPU knockdown in LUAD cells. Moreover, CENPU's coiled-coil domain was essential for CENPU's phenotypic effects in LUAD cells. In conclusion, the kinetochore component CENPU plays a critical role in LUAD cell proliferation and invasiveness. Targeting CENPU-DNAJC10 axis may inhibit LUAD tumor cell proliferation and metastasis. Highlights: CENPU mRNA and protein expression were elevated in LUAD tumors. CENPU knockdown inhibited proliferation, migration, invasion, and EMT in LUAD cells. CENPU -regulated genes were significantly enriched for proliferation and apoptosis pathways. DNAJC10 overexpression rescued the effects of CENPU knockdown in LUAD cells. CENPU's coiled-coil domain was essential for CENPU's effects on LUAD cells.